Fair Secure Roman Dominating Function in Graphs - Leomarich Casinillo; Emily L. Casinillo (Department of Mathematics, Faculty of Sciences and Technology, UIN Syarif Hidayatullah, 2026)
Let G=(V(G),E(G)) be a graph and let ϕ:V(G)→0,1,2 be a function on G. For each i∈0,1,2, let V_i=v∈V(G):ϕ(v)=i. Then ϕ can be represented as ϕ=(V_0,V_1,V_2). A function ϕ is a fair secure Roman dominating function (FScRDF) on G provided that for every v∈V_0, there exists u∈V_2 such that d_G (u,v)=1, ϕ^*=(V_0∖v,